Barriers to European growth : a transatlantic view - Lawrence, Robert Z.; Schultze, Charles L.; Brookings Institution (Washington, D.C. : Brookings Institution, 1987)
This book deals with the barriers to European growth.
Papers presented at a conference held at Brookings in October 1986.
Includes bibliographical references and index.
oo 24/09/2018
Loans
Keywords: Economic policy; Economic conditions; Europe